Sustainability and Emiratization in the UAE private banking sector: Opportunities, challenges, and future research directions - Robani, Anidah; Mohammed Alblooshi, Omran Ali Hussain (Human Resource Management Academic Research Society, 2024)
The private banking sector in the UAE is pivotal for driving economic development, generating employment, and enhancing the nation’s financial stability and global competitiveness. Despite its significant role, there is a noticeable gap in understanding the sector's current opportunities, challenges, and sustainability aspects. This review paper employs a comprehensive analytical approach to bridge this gap by systematically examining the sector's dynamics, with a particular emphasis on Emiratization and its implications for long-term success. Our analysis highlights key opportunities for growth, including the expansion into technology sectors, the development of a skilled workforce through strategic partnerships between banks and educational institutions, and leveraging government incentives to boost Emiratization. Additionally, we explore the transformative potential of digital technologies within the sector. However, the sector also faces notable challenges such as skill mismatches, insufficient practical experience, high turnover rates, and educational gaps. The study reveals that the sustainability of Emiratization initiatives is heavily influenced by factors such as bank ownership structures, stakeholder engagement, and the effective integration of local talent. To address these issues and enhance the sector's future viability, further research should focus on identifying and understanding the stakeholder dynamics that impact Emiratization and the broader sectoral development. This will provide valuable insights for policymakers, financial institutions, and educational entities striving to align with the evolving needs of the UAE's private banking sector.